Evaluating risk management practices on performance of corporates: a case of listed mining entities in Zimbabwe. - Tyoka, Simukai Gladstone (Midlands State University, 2017)
The research project sought to evaluate risk management practices on performance of listed mining entities in Zimbabwe for the period December 2015 to March 2017. Copious of the risk management research was focused on difficulties and not solutions and no one organization was in charge of managing these risk issues to get a comprehensive view of risk. This prompted the researcher to evaluate the risk management frameworks used by listed mining corporate entities as a way to gain insights to their competitive advantage on overall performance. The research objectives sought to identify risk management frameworks that have been applied to the mining sector, controls designed and operating on the established risk management frameworks, identify challenges experienced in implementing the risk management frameworks, and identify best practices which are being pursued in the mining sector for creating effective risk management frameworks. A mixed methodology approach was employed to provide information on the premise of objectivity by combining qualitative and quantitative methods for a broader perspective in evaluating risk management practices in the mining sector. Likert scale questionnaires, interviews, publications and management reports were used as the research instruments. A sample of 14 senior to middle level management employees was identified using purposeful judgement sampling, a non-probability sampling technique. Statistical Package for Social Sciences (SPSS) software was used to organise and analyse raw data gathered from participants. It was found that the effective application of risk management principles early lays the foundation for good relationships throughout the whole mine life cycle. The study also established that mines are generally not capable to implement a fully integrated risk management framework as there are hurdles to overcome that include Information Communication Technology (ICT) support, skills flight and raplex external factors affecting the sector as a whole. The study recommends that mining entities should establish a risk universe approach to risk management with a comprehensive view of risks that promotes an aligned analysis of risks across all parts on the business rather than stick to one methodology approach. Viewing risks from a global approach will add the value of research to literature and allow those charged with governance identify key business risks on an ongoing basis to develop an organisation specific risk universe that is benchmarked against other frameworks. Future work may be needed to examine the impact of risk assessment methodologies on cultivating firm value.